Magnetic resonance elastography of brain: Comparison between anisotropic and isotropic stiffness and its correlation to age. Issue 2 (8th April 2019) - Kalra, Prateek; Raterman, Brian; Mo, Xiaokui; Kolipaka, Arunark
Abstract : Purpose: Noninvasive measurement of mechanical properties of brain tissue using magnetic resonance elastography (MRE) has been a promising method for investigating neurologic disorders such as multiple sclerosis, hydrocephalus, and Alzheimer's. However, because of the regional and directional dependency of brain stiffness, estimating anisotropic stiffness is important. This study investigates isotropic and anisotropic stiffness as a function of age as well as the correlation between isotropic and anisotropic stiffness. Methods: MRE and diffusion tensor imaging (DTI) were performed on 28 healthy subjects with age ranges between 18–62 y. Isotropic and anisotropic stiffness was measured and compared with age for different regions of interest such as the thalamus, corpus callosum, gray matter, white matter, and whole brain. Results: Isotropic stiffness in gray matter (rs = −0.57; P = 0.001) showed a significant decrease with age. Anisotropic stiffness in gray matter showed a significant decrease with age in C11 through C66 and in the thalamus, only in C33 . Between anisotropic and isotropic stiffness, gray matter showed a significant positive correlation in C11 through C66, C22 and C66 showed a significant negative correlation in the thalamus and whole brain, and C44 showed a negative correlation in the corpus callosum. No significant difference between genders was observed in any measurements. Conclusion: This study demonstrated a change in isotropic and anisotropic stiffness with age in different regions of the brain along with a correlation of anisotropic stiffness to isotropic stiffness.